Blood transfusion‐induced posterior reversible encephalopathy syndrome with periodic sharp wave complexes, 14‐3‐3 protein elevation, and the pulvinar sign. Issue 1 (23rd November 2020) - Shiraishi, Wataru; Yamaguchi, Takahiro; Fujiki, Ryosuke; Furuta, Konosuke
Abstract: A 52‐year‐old Japanese woman was admitted to our hospital with consciousness disturbance and convulsions at 10 days after transfusion with 10 U of blood due to severe anemia. Electroencephalography showed periodic sharp wave complexes, cerebrospinal fluid 14‐3‐3 protein levels were elevated, and brain magnetic resonance imaging demonstrated bilateral thalamic hyperintensity. These findings suggested Creutzfeldt‐Jakob disease (CJD); however, her symptoms were resolved with antiepileptic and anti‐hypertensive drugs. We herein report a case of posterior reversible encephalopathy syndrome that occurred after a blood transfusion who showed features compatible with CJD.